2014
DOI: 10.3844/ajassp.2014.700.706
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Steel Slag Aggregate on Mechanical Properties of Concrete

Abstract: This study presents an evaluation of the physical and mechanical properties and characteristics of steel slag aggregate concrete in comparison with the typical crushed limestone stone aggregate concrete. Hardened concrete consist of more than 70% aggregate due to the high demand in building construction and the increase of the amount of disposed waste material, suppliers and researchers are exploring the use of alternative materials which could preserve natural sources and save the environment. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…However, these two SFS aggregate sources reduced the split tensile strength relative to the control concrete. These findings agree with the literature in that SFS aggregates can increase [18,20,22,34,42,56,57,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] or decrease [16,59,[87][88][89] the compressive strength and similarly increase [18,20,22,42,57,70,[72][73][74]76,79,82,85,90,91] or decrease [75,80,89] …”
Section: Concrete With Sfs Aggregatessupporting
confidence: 92%
“…However, these two SFS aggregate sources reduced the split tensile strength relative to the control concrete. These findings agree with the literature in that SFS aggregates can increase [18,20,22,34,42,56,57,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] or decrease [16,59,[87][88][89] the compressive strength and similarly increase [18,20,22,42,57,70,[72][73][74]76,79,82,85,90,91] or decrease [75,80,89] …”
Section: Concrete With Sfs Aggregatessupporting
confidence: 92%
“…Thus, this experimental study is carried out replacing the natural coarse aggregate in cement-less geopolymer concrete by scrap steel slag, an industrial waste. 1 studied the effects of using steel slag aggregate on mechanical properties of concrete and reports that steel slag acts as accelerator at early age and 7 days strength of steel slag concrete is higher and at 28 days, the effect is reduced. 2) Mohammed Nadeem, Arun Pofale (2012) 2 investigated use of different types of steel slag as coarse in concrete and reports that steel slag absorbs lesser water than brick aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…One of the potential resources of recycled concrete is steel slag, knowing that steel slag is the most significant solid waste generated by Qatar Steel Company in Qatar [1]. Several researchers have shown that steel slag can be used as an aggregate in structural concrete [2][3][4][5][6]. The use of steel slag in concrete applications has major economic and environmental benefits to Qatar.…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of publications have contradicted this idea [3][4][5][6]. Recently, a number of researchers studied the possibility of using steel slag in concrete mixes as a coarse aggregate to make sustainable concrete [3][4].…”
Section: Introductionmentioning
confidence: 99%